Shock-induced time-dependent strength behavior in amorphous alloys from a microscopic view. (15th July 2016) - Chen, Kaiguo; Yu, Yuying; Zhang, Zugen; Shi, San-Qiang
Abstract: Shock-induced strength behavior and the corresponding microstructural evolution have remained unclear for decades. We propose a viscous-solid model from a microscopic view implied by simulations with non-equilibrium molecular dynamics. The model describes the shocked microstructure very well and shows time-dependent strength behavior upon shock-induced yielding in amorphous alloys. For the first time, we find that the Kohlrausch-Williams-Watts equation [ φ ( t ) = e −( t /) β ] is quantitatively applicable in the modelling of time-dependent strength behavior at the non-equilibrium shockwave front. The parameters in the Kohlrausch-Williams-Watts equation are found to agree well with several experimental facts. Graphical abstract: